Kesejahteraan subjektif warga tua di Malaysia: kes warga tua desa Kelantan - Wan Ahmad, Wan Ibrahim; Redzuan, Ma'arof; Emby, Zahid; Hamid, Abdul Halin (Universiti Utara Malaysia, 2009)
Purpose – Within the gerontological kepustakaane, human and social capitals have been widely assumed to enhance subjective well-being of the elderly. The objective of this study was to identify the extent to which well-being of rural elderly is being influenced by their human and social capitals. Design/Methodology/Approach – To acheive this objective, 214 people aged 60 years and above in rural Kelantan were selected. Using data from the survey,14 demographic and social variables were analysed using multiple regression analysis to determine their influence on the well-being of the elderly people. Findings – Results showed that education, work experience, housing, and social ties with spouses, friends, and neighbours are variables that have a significant influence on the subjective well-being of the elderly within the study area. Originality/Value – This study conformed that education, work experiences, housing, and social ties with spouses, friends, and neighbours are significantly important for the subjective well-being of the elderly.